Pengembangan Aplikasi Web Pencarian Pasangan Untuk Kucing - Alya Quinta Aqilah (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to produce a web-based mate search application for cats experiencing estrous cycles. The software development method used in this research is the Rational Unified Process (RUP) with Unified Modeling Language (UML) modeling. This application is built on a web basis with the programming languages HTML, PHP, CSS, JavaScript, and uses MySQL as a database and CodeIgniter as a framework. The web-based partner search app for cats provides an alternative to partner search for cats experiencing an estrous cycle and having to mate. Searching for cat mates can be done by searching on an application connected to the internet and connected to the Global Positioning System (GPS), then the details cat information will appear along with the cat's location with a marker on the map which can reveal the cat owner's full address and also access to contact cat owners via WhatsApp. Based on the UAT test, the results of this study are proven to be used as an alternative application in the process of finding a partner for cats experiencing an estrous cycle. The result of this research is a match search web application for cats.